Introduction to AI techniques for renewable energy systems - Tripathi, Suman Lata (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
"The book summarizes commonly used AI methodologies in renewal energy, with a particular emphasis on neural networks, fuzzy logic, and genetic algorithms. Book outlines selected AI applications for renewable energy. In particular, discusses methods using the AI approach for the following applications using suitable examples: prediction and modeling of solar radiation, seizing, performances, and controls of the solar photovoltaic (PV) systems"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Renewable energy sources; Power-plants -- Automatic control; Artificial intelligence